(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2024)
The article discusses a method for digitally signing document images without using metadata or additional files. The method is resistant to jpeg compression within certain limits. The object of the digital signature is 8x8 pixel blocks with a discrete cosine transform applied, which make up the jpeg file. A method to achieve resistance to jpeg compression is to quantize (reduce the precision) the values in the blocks so that when the signature is calculated, they remain unchanged up to a certain compression level. The study presents a robust method for digitally signing JPEG images that remains effective despite compression. This method is particularly useful for verifying the authenticity of document images in electronic document management systems without requiring extensive infrastructure or certification processes.